Examination of articles on management processes by the method of bibliometric analysis during the COVID-19 pandemic period - Demir Uslu, Yeter; Hancıoğlu, Yasemin (Mehmet Akif Ersoy University, 2022)
With the COVID-19 pandemic process, quarantine and isolation procedures, preventive health services, therapeutic health services and basic health services have become one of the priority objectives of health systems. The necessity of organizing health systems quickly and effectively by adapting to the new situation has emerged. The rapidly changing nature of COVID-19 has led to a reassessment of how healthcare organizations create their strategies, organize and manage the process. The aim of the study is to examine the articles dealing with COVID-19 management processes by the bibliometric analysis method according to the determined criteria. The 81 articles were analyzed with graphs and tables according to the criteria of country, year and month of publication, number of authors, research methods, fields of study, topics covered and descriptive characteristics. When the analysis results are examined, it is seen that the country in which the articles are published the most is Turkey (49.38%), 85.19% of the articles are multi-authored, 62.96% of them are compilations, the study areas are region, country, development level, various institutions, On the other hand, it is seen that the subjects that are discussed more in the study subjects such as patients, sectors, and literature are management processes, human resources management, crisis management, risk management, and waste management.It is thought that the results of the study will guide the subsequent studies.

COVID-19 pandemi süreciyle birlikte karantina ve tecrit prosedürleri, koruyucu sağlık hizmetleri, tedavi edici sağlık hizmetleri ve temel sağlık hizmetlerinin sekteye uğramaması, sağlık sistemlerinin öncelikli amaçlarından biri haline gelmiştir. Sağlık sistemlerinin yeni duruma adapte olarak hızlı ve etkili bir şekilde organize edilmesi gerekliliği ortaya çıkmıştır. COVID-19’un hızla değişen doğası, sağlık kuruluşlarının stratejilerini nasıl oluşturduğu, süreci nasıl organize ettiği ve yönettiği konusunda yeniden değerlendirme yapmayı beraberinde getirmiştir. Çalışmanın amacı, COVID-19 yönetim süreçlerini ele alan makalelerin belirlenen kriterlere göre bibliyometrik analiz yöntemi ile incelenmesidir. 81 makale, ülke, yayın yılı ve ayı, yazar sayıları, araştırma yöntemleri, çalışma alanları, ele alınan konular ve tanımlayıcı özellikler kriterlerine göre grafik ve tablolarla analiz edilmiştir. Analiz sonuçları incelendiğinde, makalelerin en fazla yayınlandığı ülkenin Türkiye (%49,38) olduğu, makalelerin %85,19’unun çok yazarlı oluğu, %62,96’sının derleme olduğu, çalışma alanlarının bölge, ülke, gelişmişlik düzeyi, çeşitli kurumlar, hastalar, sektörler, yazınlar olduğu, çalışma konularında ise daha fazla ele alınanların ise yönetim süreçleri, insan kaynakları yönetimi, kriz yönetimi, risk yönetimi, atık yönetimi olduğu görülmektedir. Çalışmanın sonuçlarının bundan sonraki çalışmalara yol gösterici olacağı düşünülmektedir.
COVID-19 pandemi döneminde yönetim süreçleri ile ilgili makalelerin bibliyometrik analiz yöntemiyle incelenmesi
Keywords: Bibliometric Analysis; COVID-19; Management Processes; Health Management; Bibliyometrik Analiz; COVID-19; Yönetim Süreçleri; Sağlık Yönetimi